Beyond Legal Origin and Checks and Balances : Political Credibility, Citizen Information, and Financial Sector Development - Keefer, Philip (World Bank, Washington, DC, 2012)
The existing literature emphasizes and contrasts the role of political checks and balances and legal origin in determining the pace of financial sector development. This paper expands substantially on one aspect of this debate: the fact that government actions that promote financial sector development, whether prudent financial regulation or secure property and contract rights, are public goods and sensitive to political incentives to provide public goods. Tests of hypotheses emanating from this argument yield four new conclusions. First, two key determinants of those incentives-the credibility of pre-electoral political promises and citizen information about politician decisions-systematically promote financial sector development. Second, these political factors, along with political checks and balances, operate in part through their influence on the security of property rights, an argument asserted but not previously tested. Third, contrary to findings elsewhere in the literature, the political determinants of financial sector development are significant even in the presence of controls for legal origin. Finally, and again in contrast to the literature, the evidence here suggests that legal origin primarily proxies for political phenomena. Legal origin is a largely insignificant determinant of financial sector development when those phenomena are fully taken into account.